2015
DOI: 10.1016/j.ijmecsci.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the effects of shear deformation and superimposed hydrostatic pressure on the formability of AZ31B sheet at room temperature

Abstract: The effect of the shear deformation and the superimposed hydrostatic pressure on the formability of magnesium alloy sheet is simulated in terms of the forming limit diagram (FLD). The model employed is the elastic viscoplastic selfconsistent (EVPSC) crystal plasticity model, which accounts for both slip and twinning systems as the deformation mechanisms. The conventional sheets have low formability at room temperature due to the strong basal texture developed by the rolling process. However differential speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…They found that the fatigue failure curve of rock salt was controlled by the complete stress-strain curve under static loading. Similar results have been obtained with rock of different densities, such as marble [10][11][12][13], granite [14,15], white sandstone [16], and coal rock [17] through fatigue testing. It was suggested that fatigue testing would be a feasible and effective method for damage evolution.…”
Section: Introductionsupporting
confidence: 81%
“…They found that the fatigue failure curve of rock salt was controlled by the complete stress-strain curve under static loading. Similar results have been obtained with rock of different densities, such as marble [10][11][12][13], granite [14,15], white sandstone [16], and coal rock [17] through fatigue testing. It was suggested that fatigue testing would be a feasible and effective method for damage evolution.…”
Section: Introductionsupporting
confidence: 81%
“…From these literatures [12][13][14][15][16][17][18][19][20], it is concluded that the observed difference in biaxial and hemispherical dome test failure points in the present research can be explained by the pressurization effect that the punch has on the specimen during hemispherical dome forming. This effect is not present in specimens pulled on the biaxial machine, and, therefore, the ductility is not affected, and a lower formability and failure is seen.…”
Section: Resultsmentioning
confidence: 54%
“…The main difference in the hemispherical dome test as compared to the biaxial test is that the punch is in contact with the sheet metal, and it forces downward in order to deform the material by pressurizing the sheet surface. It is assumed that this difference is making the material deform more during the hemispherical dome tests than was found with the Some previous research [12][13][14][15][16][17][18][19][20] has observed that the application of pressure through the thickness direction can soften the material and increase its forming. As investigated in these literatures, the effect of pressurization on formability in sheet metals is a case that an effective softening of the material occurs to varying degrees, depending upon the amount of pressure that is applied to a given material through thickness direction.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This is an unwanted variable that can cause variations in testing and data collection [25][26][27]. Pressure is the other contact condition that can cause the sample to fail at higher forces or time because of how the pressure makes the material behave while under stress [28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%